Personal Data Protection in Banking Cybersecurity Breach Cases: Perlindungan Data Pribadi dalam Kasus Pelanggaran Keamanan Siber di Sektor Perbankan - Angelina Septiani Zaroh; Sri Budi Purwaningsih (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The rapid digitalization of banking services has increased the risk of cyber threats and unauthorized access to personal data. Specific Background Several cases of data breaches in Indonesian banking institutions highlight vulnerabilities in safeguarding customer information and raise concerns regarding legal protection mechanisms. Knowledge Gap However, limited studies analyze the legal responsibility of banks and the adequacy of personal data protection regulations in addressing such breaches. Aims This study aims to examine the legal framework governing personal data protection and analyze the accountability of banking institutions in cases of data breaches. Results The findings indicate that although regulations such as the Personal Data Protection Law provide a legal basis, challenges remain in enforcement and implementation, particularly in ensuring accountability and compensation for affected customers. Novelty This study emphasizes the relationship between cybersecurity incidents and legal liability within the Indonesian banking sector. Implications The results suggest the need for stronger regulatory enforcement and improved institutional compliance to ensure better protection of customer data in digital banking environments. Keywords: Personal Data, Banking Security, Cybercrime, Legal Protection, Data Breach Key Findings Highlights Cyber incidents reveal weaknesses in institutional safeguards Regulatory provisions exist but enforcement remains limited Customer rights require stronger legal assurance